Variations in the start, end, and length of extreme precipitation period across China - Xiangyu Guo; Zhengfang Wu; Hongshi He; Haibo Du; Lei Wang; Yue Yang; Weihong Zhao (International Journal of Climatology, 2018)
Using the daily precipitation records during 1961–2013 from 686 meteorological stations across China and the atmospheric circulation indexes, this study investigates the spatio‐temporal changes in the occurrence time and length of the extreme precipitation period (EPP), as well as their influencing factors. The results show the following aspects: (1) In the last 53 years, the start dates of the extreme precipitation period (EPPS) generally advanced. The end dates of the extreme precipitation period (EPPE) are delayed, which show an increasing trend. The lengths of the extreme precipitation period (EPPL) in most of the China meteorological stations increased. (2) The spatial patterns of the trends in the occurrence time and length of the extreme precipitation period are similar and show obvious clustering. The occurrence time and length of the extreme precipitation period have obvious spatial gradient differences in their average values. In southeastern China, the average EPPS is earlier, EPPE is later than those in other regions, and their EPPL is prolonged. The EPP in northeastern China begins later and ends earlier, and its EPPL is shorter than that in other regions. (3) The western Pacific subtropical high, Northern Hemisphere polar vortex, Antarctic Oscillation, and western Pacific warm pool have significant effects on the occurrence time and length of EPP over China, and different regions show different effects.